Floating Serv Ability Volleyball Skill: the Relationship of Muscle Strength for Junior High School - Nazirah, Nazirah (INSPIREE: Indonesian Sport Innovation Review, 2024)
The  purpose  of  the study. The purpose of this study was to determine the relationship between arm muscle strength and the results of the volleyball floating serve for students of Junior High School. Materials and methods. The form of this study is a correlation study with the population ofstudents of Junior High School, Kampar Regency with a total sample students. The instruments used in this study were the arm muscle strength test and the floating exercise. Results. Data analysis in this study obtained r count of 0.902 with a large  contribution of 81.36%, this is classified as very good. Based on the results of the research  conducted.  Conclusions. Where  obtained r arithmetic = 0.902>rtable=0.576 with a contribution of 81.36%. concluded that there is a relationship between arm muscle strength and the  ability of the Junior High School to have a floating servi